0670 The role of social vigilance and hindrance-challenge stress in predicting nightmares among nurses. (25th May 2022) - Jordan, Saylor; Slavish, Danica; Dietch, Jessica; Messman, Brett; Taylor, Daniel; Kelly, Kimberly; Ruggero, Camilo; Haynes, Patricia; Ruiz, John
Abstract: Introduction: Increased exposure and reactivity to daytime stressors may heighten the frequency and severity of nightmares. Although research has examined the role of personality traits such as neuroticism in nightmares, it is unknown if other hypervigilance-related characteristics predict nightmares. Social vigilance, or monitoring one's social environment for potential threats, is one factor that may influence stress reactivity and sleep. Nurses are one population who may be particularly susceptible to social vigilance and nightmares given their stressful work environments. The current study had two aims: 1) to examine the association between social vigilance and nightmares (assessed via retrospective questionnaire and via daily sleep diaries), and 2) to examine if perceived job stress strengthened the association between social vigilance and nightmares. Methods: Participants were 464 nurses (mean age = 39.03 years, SD = 11.07 years, 91% female) recruited from two Dallas-area hospitals. At baseline, nurses completed the Social Vigilance Questionnaire (SVQ), the Nightmare Disorder Index (NDI; a newly validated scale measuring past-month nightmare frequency and severity), and the Challenge- and Hindrance-Related Self-Reported Stress Scale (CHRSS). Nurses then completed 14 days of sleep diaries to assess daily nightmare frequency, which were then summed across the 14 days. Multiple linear regression models were run to assess main effects of social vigilance and hindrance or challenge stress, as well as their interactions, on nightmares. Results: Greater social vigilance (β = 0.10, p = 0.041) and greater hindrance stress (β = 0.13, p = 0.031) each predicted more nightmare symptoms as measured by the NDI, but not nightmare frequency as measured by the daily surveys. Only greater hindrance stress predicted greater daily nightmare frequency as measured by the daily surveys (β = 0.14, p = 0.015). Social vigilance did not interact with either hindrance or challenge stress to predict nightmares. Conclusion: Results indicate nurses who report higher levels of social vigilance or hindrance stress at work experience more nightmare symptoms. Although more research is needed, supporting nurses who report high levels of stress and vigilance may help reduce their arousal and improve their sleep. Support (If Any): 1R01AI128359